2019
DOI: 10.9734/afsj/2019/v10i130024
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Light Influence on the Walnuts Oil Quality

Abstract: This paper represents a statistical processing of experimental studies on the influence of light on the quality of nut oil (Juglans regia L). The conformity of nut oil Calaras and Kogalniceanu, harvested in 2013 and 2015, was analyzed in the Republic of Moldova. The objective of this study was to determine effect of storage conditions (stored at light and dark) on the stability of walnut oil during storage by measuring the Peroxide Values (PV), Acid values (AV), Kinetic Study of Lypid Peroxidation A (PV), Reic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The results showed an increase in the acid value during storage for all samples give varying degrees. The result was before storage is 0.16 mg / KOH gm of oil, this result is close to the limits reported by Sandulachi et al (2019) that the acid value of walnut oil ranges from 0.17 mg / KOH gm oil -5.05 mg / KOH gm oil) and close to the value mentioned by Gharibzahedi et al (2012) that the acid value of walnut oil ranges from 0.12 mg/KOH gm oil -0.14 mg/KOH gm oil, while it does not agree with what Popovici et al (2012) found that the acid value of walnut oil is 0.94 mg/KOH gm oil, and it does not agree with what was mentioned by Martinez et al (2013). that the acid value of walnut oil is 0.08 mg / KOH gm of oil, and this difference may be attributed to genetic factors, different varieties, breeding conditions and estimation methods used to estimate this trait.…”
Section: Acid Valuesupporting
confidence: 91%
“…The results showed an increase in the acid value during storage for all samples give varying degrees. The result was before storage is 0.16 mg / KOH gm of oil, this result is close to the limits reported by Sandulachi et al (2019) that the acid value of walnut oil ranges from 0.17 mg / KOH gm oil -5.05 mg / KOH gm oil) and close to the value mentioned by Gharibzahedi et al (2012) that the acid value of walnut oil ranges from 0.12 mg/KOH gm oil -0.14 mg/KOH gm oil, while it does not agree with what Popovici et al (2012) found that the acid value of walnut oil is 0.94 mg/KOH gm oil, and it does not agree with what was mentioned by Martinez et al (2013). that the acid value of walnut oil is 0.08 mg / KOH gm of oil, and this difference may be attributed to genetic factors, different varieties, breeding conditions and estimation methods used to estimate this trait.…”
Section: Acid Valuesupporting
confidence: 91%
“…Rancimat method was developed by Hadorn and Zurcher (1974) [ 7 ] to measure oxidative stability and has been widely used to determine lipid oxidation and predict the shelf life of oils and fats [ 8 ]. This method has been vastly used to study the effects of antioxidants, edible coatings, and storage conditions of nut oils [ 9 , 10 , 11 ]. However, measuring oxidative stability through an accelerated method can lead to an over or underprediction of the actual shelf life due to different mechanisms of peroxidation that occur at room temperature [ 4 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important elements in industrial refining process and also in marketing is the color of edible oils. (Fengxia, Dishun et al 2001) To this aim, a combination of digital camera, computer, and graphics software set up to measure and determine the color of HCM oil, based on the L*a*b* format according to (AOCS Cc 13c-50)(Sandulachi and Tatarov 2014). Instrument calibration was set by the zero calibration box and the white calibration plate, used for total color difference calculation.…”
Section: Methodsmentioning
confidence: 99%